2019
DOI: 10.1080/10717544.2018.1534898
|View full text |Cite
|
Sign up to set email alerts
|

Efficient exosome delivery in refractory tissues assisted by ultrasound-targeted microbubble destruction

Abstract: Recently, exosomes have been emerged as promising drug delivery carriers, while certain tissues are intrinsically resistant to exosomes. Therapeutically improving the drug delivery efficiency in these tissues/organs would certainly broaden the potential application of exosomes in future. Ultrasound-targeted microbubble destruction (UTMD) is a promising technique for non-invasive, targeted drug delivery. In this study, we explore the possibility that UTMD assists exosome delivery in these intrinsically resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 28 publications
3
39
0
Order By: Relevance
“…In regard with the specific working mechanism of exosomes, there is still a lot of work to do. Although we have demonstrated that exosomes predominately accumulate in liver after intravenous injection which is consistent with other researches, there are still a small population of exosomes that will circulate into heart and WAT 50 , 51 . It is thus no doubt that some BAT-Exos could affect and regulate WAT and heart directly.…”
Section: Discussionsupporting
confidence: 91%
“…In regard with the specific working mechanism of exosomes, there is still a lot of work to do. Although we have demonstrated that exosomes predominately accumulate in liver after intravenous injection which is consistent with other researches, there are still a small population of exosomes that will circulate into heart and WAT 50 , 51 . It is thus no doubt that some BAT-Exos could affect and regulate WAT and heart directly.…”
Section: Discussionsupporting
confidence: 91%
“…Aside from using exosome-embedded hydrogels to achieve a topical and sustained drug release effect, when exosomes are not encapsulated in hydrogels, they are delivered intravenously or topically [ 80 ]. Sun and co-authors [ 80 ] have designed a delivery method that can topically release exosome at the target sites.…”
Section: Alternative Methods To Exosome Deliverymentioning
confidence: 99%
“…Aside from using exosome-embedded hydrogels to achieve a topical and sustained drug release effect, when exosomes are not encapsulated in hydrogels, they are delivered intravenously or topically [ 80 ]. Sun and co-authors [ 80 ] have designed a delivery method that can topically release exosome at the target sites. They also intravenously injected exosomes together with a SonoVue TM microbubble (Bracco Imaging) into mice, and then targeted the destruction of these microbubbles by ultrasound [ 80 ].…”
Section: Alternative Methods To Exosome Deliverymentioning
confidence: 99%
“…However, this approach did not have the desired effects and it has only been used for restricted applications. [187] In their paper, the authors demonstrated the possibility of loading EVs into mice refractory tissues by injecting SonoVue (sulfur hexafluoride) microbubbles together with the EVs and inducing UTMD. Microbubble destruction and the cavitation effect increased the infiltration of EVs in heart, adipose tissue, and skeletal muscles, as well as in liver and the reticuloendothelial system, [187] opening another promising way to increase the selectivity of EV targeting.…”
Section: Other Delivery Avenuesmentioning
confidence: 99%
“…Indeed, given their higher flexibility in production and easier functionalization, polymersomes can be envisaged as an advantageous and cheaper alternative to liposomes. Extracellular vesicles + Difficult massive production and purification; biomolecules as only building blocks; limited tunability of the physicochemical properties [ 87,240] +++ Generally safe; extraction from biological sources with high biocompatibility [80,83] ++ Excellent loading of biomolecules; challenging loading of synthetic molecules; good delivery efficiency;rapid clearance [ 186,187] Liposomes ++ Easy production and purification; pre-and postsynthetic functionalization; tunable physicochemical properties [ 124,161] +++ Generally safe, unless modified with charged phospholipids; similar composition to EVs, but without cell-mediated modifications [103,213] ++ Good natural and synthetic molecules loading; preassembly and postassembly loading; good delivery efficiency; tunable clearance properties [ 198,199] Polymersomes +++ Customizable massive production; pre-and postsynthetic functionalization; tunable physicochemical properties [ 136,155] + Possible accumulations in the body; possibility to introduce biodegradable polymers [229,230] + Preassembly and postassembly loading; cell uptake dependent on the vesicle and cell membrane characteristic; tunable clearance properties [ 222,224]…”
Section: Productionmentioning
confidence: 99%